Blood concentration of levetiracetam after bolus administration in patients with status epilepticus. (July 2021) - Nagano, Makihiko; Tagami, Takashi; Kaneko, Junya; Kondo, Masayoshi; Hotta, Mio; Kubota, Minoru; Sugaya, Kazutoshi; Takase, Hisamitsu; Kuno, Masamune; Unemoto, Kyoko
Highlights: After bolus (2500 mg), LEV blood concentration reached the therapeutic range Seizure suppression was observed in over 90% of patients Few adverse events were noted and no severe adverse effect was observed These results indicate the effectiveness of LEV as a second-line drug for SE Abstract: Purpose: We aimed to evaluate the blood concentration of levetiracetam (LEV), as a second-line drug, in patients with status epilepticus (SE) in an emergency clinical setting. Methods: We prospectively evaluated 20 consecutive patients with SE admitted to our department between July 2017 and July 2019. LEV (2500 mg) was administered via bolus infusion after diazepam infusion, followed by 500 mg every 12 h for 48 h and then 500 mg orally. The primary outcomes were LEV blood concentration 15 min, 12 h, 48 h, and 96 h after administration and the proportion of patients showing trough LEV concentration within the therapeutic range. The secondary outcomes were the discontinuation of apparent convulsive seizure, epileptic wave on electroencephalogram, tracheal intubation, adverse events related to blood parameters, and abnormal findings in vital signs examination. Results: Median blood LEV (2500 mg) concentration at 15 min after administration was 81.6 μg/mL. The median trough concentration after 12, 48, and 96 h was 28.8, 10.5, and 9.1 μg/mL, respectively. Moreover, 95% of patients had trough concentration above the lower limit of the therapeutic blood concentration (>12 μg/mL) after 12 h. Regarding secondary outcomes, endotracheal intubation, seizure suppression, and abnormal electroencephalogram findings were observed in approximately 40%, 90%–95%, and 41% of patients, respectively. No abnormal findings were noted in blood tests and vital sign examination, although the AST/ALT levels increased in 10% of the patients. Conclusion: After bolus administration of 2500 mg, the blood LEV concentration reached the therapeutic window in patients with early-stage SE. Graphical Abstract: Image, graphical abstract